Climate-related partial relocation in Fiji impacts the wellbeing of those who relocated and those who stayed differently - Link, Ann-Christine; Piggott-McKellar, Annah; Nakoro, Elia; Oakes, Robert (Communications earth & environment, 2025)
Climate change threatens habitability, leading communities to relocate out of sites of high exposure. Partial relocations, whereby only a portion of the community relocates, are understudied but increasingly common as relocating in one move is not always possible nor necessarily desired. Drawing on two climate-related partial relocations in Fiji—one community-driven, currently underway, and one government-assisted, undertaken ten years ago—we use Q Method to explore subjective wellbeing outcomes and identify shared narratives across the two communities. We find that partial relocation continues to strongly shape the wellbeing and lives of individuals, even ten years after relocating, and highlights different outcomes  between those who relocated and those who did not. We argue that these shared narratives are strategic tools that can be drawn upon to understand nuanced experiences, shape people-centred policies, and, ultimately, inform relocation efforts that are more just, effective, and sustainable.
Gesehen am 19.01.2026